Anti-diuretic and anti-glycemic properties of Jatropha gossypiifolia L. leave extract on wistar rats - Benjamin Ogunma Gabriel (SpringerOpen, 2021)
Abstract Background Jatropha gossypiifolia L. is a widespread plant in tropical and sub-tropical countries used in traditional medicine. This study investigated the anti-diuretic and anti-hyperglycemia activities of J. gossypiifolia leave extract on streptozotocin-induced diabetic rats. Methods The leaves was shade dried, pulverized and prepared into extract. 30, 50 and 100 mg/kg of the leaves extracts of J. gossypiifolia was subject to diuretics and hyperglycemic properties using established protocol of diuretic and diabetes test on the rat bladders emptied via mild compression in the pelvic region and gently pulling of their tails. 0.5 ml/kg normal saline, reference drug and the tested were administered with a single dose of the various drugs, and Streptozotocin (STZ) was freshly prepared in 0.1 M citrate buffer with pH 4.5 prior to induction, animals were fasted 24 h and single dose of 45 mg STZ per kg body weight was administered intraperitoneally. Urine and blood samples were isolated from rats and centrifuged for the determination of renal function test. Diuretic and antidiabetic indexes where evaluated using adopted method. Results This study showed that, graded doses of the extract significantly increased diuretic effect, specifically at 100 mg/kg increased diuretic index at 4.29 and urine volume 5.06 and 10 mg/kg Hydrochlorothiazide with 6.23 ml when compared untreated group (1.18 ml) (p < 0.0001). Also, it regulated renal function in homeostatic state. Graded doses at (30, 50 and 100 mg/kg) of the extract significantly reduced streptozotocine induced increased blood glucose level at day 14 (84.00, 60.67 and 42.00 IU/mL) when compared with 20 mg/kg glibenclamide and diabetics control (81.67 and 463.00 IU/mL) (p > 0.05). Also, the extract maintained a normal body mass indexes, biochemical and anatomical structure. Conclusion The effect associated with J. gossypiifolia potentiated its anti-diuretic and anti-hyperglycemic properties as early stated in the ethnomedicinal reports.